2015
DOI: 10.3390/antiox4030563
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Phenolic Content in Different Barley Varieties and Corresponding Malts by Liquid Chromatography-diode Array Detection-Electrospray Ionization Tandem Mass Spectrometry

Abstract: A simple and reliable method for the simultaneous determination of nine phenolic compounds in barley and malted barley was established, using liquid chromatography-diode array detection-electrospray ionization tandem mass spectrometry (HPLC-DAD-ESI-MS/MS). The phenolic compounds can be easily detected with both systems, despite significant differences in sensitivity. Concentrations approximately 180-fold lower could be achieved by mass spectrometry analysis compared to diode array detection, especially for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
55
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 33 publications
(56 reference statements)
6
55
0
Order By: Relevance
“…[6,15,18,19] The alcoholic mixtures, such as ethanol/water and methanol/water, allowed higher extraction yields of free phenols, mainly in terms of total phenolic compounds. [8,11] Therefore, in this work, ethanol was used as solvent to extract free phenolics that will be largely present in the beer during the malting process.…”
Section: Extraction Of Phenolic Compoundsmentioning
confidence: 99%
See 4 more Smart Citations
“…[6,15,18,19] The alcoholic mixtures, such as ethanol/water and methanol/water, allowed higher extraction yields of free phenols, mainly in terms of total phenolic compounds. [8,11] Therefore, in this work, ethanol was used as solvent to extract free phenolics that will be largely present in the beer during the malting process.…”
Section: Extraction Of Phenolic Compoundsmentioning
confidence: 99%
“…[27] Also, Carvalho et al [6] reported that flavanols were the major phenolic fraction in barley and malt from Portugal. In this work, PB3 (a dimeric flavanol) was found to be the most abundant phenolic compound identified in the four barley varieties with 72.63%, 72.46%, 68.19%, and 61.63% of the TPC for Swihli, Faiz, Rihane, and Manel, respectively (Fig.…”
Section: Identification and Quantification Of Phenolic Compounds By Hmentioning
confidence: 99%
See 3 more Smart Citations